Pelatihan Pemanfaatan Eco- Enzyme dalam Pemberdayaan Masyarakat - Widyaningsih, Bekti; Ashlihah; Kusuma, Saiful Aminudin Al; Muna, Naily El; Salsabila, Dini Nafisa (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
ABSTRACT Community Service Activities were carried out in Miagan Village, Mojoagung District through training on the use of Eco-Enzyme. This activity aims to provide an explanation and understanding of the use of organic waste to the public, providing knowledge about how organic waste can be utilized/reprocessed into a useful liquid, namely Eco enzyme. The approach method for implementing community service activities includes discussion, training, practice, and questions and answers directly in front of the training participants, called the Fucus Group Discussion (FGD) method. The results of the training activities on the use of eco-enzymes provided learning, assistance and empowerment regarding the manufacture of Eco-enzymes in increasing the potential of human resources and they were also able to answer the post test that had been given. Keywords: Eco-Enzyme, waste, organic